أوغسطين تاغست: الفيلسوف اللاهوتي صاحب التأثير العالمي: دراسة إستقرائية تحليلية في الفكر الأوغسطيني - دكار، إلياس بن عبدالله Dakar, Ilyas Bin Abdullah (المركز الجامعي بتندوف, 2020)
يعتبر الفيلسوف المعروف ورجل الدين الشهير في المسيحية من أصول شمال إفريقية، أوريليوس أوغيستينيوس (356م- 430م) من أشهر الفلاسفة المؤثرين في تاريخ الفكر الإنساني على الإطلاق والفكر السياسي المسيحي الكاثوليكي على الخصوص، لذلك كان من الطبيعي أن يكون نصيبه من الدراسات الأكاديمية المعتنية بفكره هائلا لمكانته الرفيعة ولكونه قد انفرد بالسيطرة على العقل الغربي لقرون عديدة حتى زاحمته في هذه السيطرة العقلانية المشائية المؤمنة؛ كان لأوغسطين الأثر الكبير في الفكر الغربي والفكر الإنساني فهو منظر التاريخ المسيحي، ومؤسس الكنيسة الدينية ومصدر الثقافة الفلسفية في بداية العصر الوسيط وعصر النهضة، كما حدد معايير الفصل بين السلطة الروحية والزمنية.
The well-known philosopher and famous cleric in Christianity of North African origins, "Aurelius Augustinius (354 AD - 430 AD)" is considered one of the most famous influential philosophers in the history of human thought at all, and Catholic Christian political thought in particular, so it was natural that his share of academic studies Caring for his idea tremendously for its high position and for being the only one controlling the Western mind for many centuries until it crowded it into this believing, peripheral rational control; Augustine had a great influence on Western thought and human thought, as he is the theorist of Christian history, the founder of the Latin Church and the source of philosophical culture in the early Middle Ages and the Renaissance, and he also defined the criteria for separating spiritual and temporal authority.
Keywords: أوغيستينيوس، أوريليوس، ت. 430 م. -- الفلسفة المسيحية -- الفلسفة التاريخية